Pengaruh Sistem Informasi Manajemen Terhadap Kinerja Karyawan Pada Pt.Astra Motor Honda Cabang Mamuju - Saputri, Riris Mega; Zafirah, Annisa Lulu (CV. SINAR HOWUHOWU, 2026)
The development of information technology has encouraged companies to optimize information systems in order to improve work effectiveness and efficiency. This article aims to analyze the influence of Management Information Systems (MIS) on employee performance at PT Astra Motor Honda Mamuju Branch based on a literature study. The research method employs a qualitative approach through a literature review, with data sources derived from scientific journals, books, and previous studies related to MIS and employee performance. The results of the review indicate that MIS plays an important role in improving data accuracy, accelerating operational processes, enhancing coordination among work units, and supporting managerial decision-making. Proper implementation of MIS also contributes to increased productivity, work discipline, and service quality of employees. This article concludes that MIS has a significant influence on employee performance when supported by adequate training, technological infrastructure, and organizational commitment.